Lithium-ion secondary battery
By forming a single integral sintered body with controlled direct contact areas, the lithium ion secondary battery addresses yield and long-term performance issues through enhanced bonding and reduced interfacial delamination, resulting in improved discharge capacity and efficiency.
Patent Information
- Application Number
- JP2022545297
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-08-26
- Filing Date
- 2021-03-29
- Publication Date
- 2025-01-23
- Estimated Expiration
- 2041-03-29
AI Technical Summary
Existing integral sintered body type lithium ion secondary batteries suffer from poor yield and long-term performance due to interfacial delamination issues, particularly at the interface between the negative electrode layer and the current collecting layer.
The positive electrode layer, ceramic separator, and negative electrode layer form a single integral sintered body with a controlled direct contact area of 45 to 90% between the current collecting layer and the negative electrode layer, ensuring strong bonding and minimizing stress-induced peeling.
This configuration enhances yield and maintains long-term performance by preventing interfacial delamination, improving discharge capacity retention and reducing resistance, thereby increasing the battery's overall efficiency.
Smart Images

Figure 0007620637000002 
Figure 0007620637000003 
Figure 0007620637000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a lithium ion secondary battery. [Background technology]
[0002] Lithium-ion secondary batteries are widely used in various devices that require charging. Many existing lithium-ion secondary batteries use a powder-dispersed positive electrode (so-called coated electrode) that is made by coating and drying a positive electrode mixture that contains a positive electrode active material, a conductive additive, a binder, etc.
[0003] In general, a powder-dispersed positive electrode contains a relatively large amount (for example, about 10% by weight) of components (binders and conductive assistants) that do not contribute to capacity, so the packing density of the lithium composite oxide as the positive electrode active material is low. For this reason, the powder-dispersed positive electrode has a large room for improvement in terms of capacity and charge / discharge efficiency. Therefore, attempts have been made to improve the capacity and charge / discharge efficiency by forming the positive electrode or the positive electrode active material layer from a lithium composite oxide sintered plate. In this case, since the positive electrode or the positive electrode active material layer does not contain a binder or conductive assistant (for example, conductive carbon), it is expected that a high capacity and good charge / discharge efficiency can be obtained by increasing the packing density of the lithium composite oxide. For example, Patent Document 1 (Patent Publication No. 5587052) discloses a positive electrode of a lithium ion secondary battery that includes a positive electrode collector and a positive electrode active material layer bonded to the positive electrode collector via a conductive bonding layer. The positive electrode active material layer is said to be made of a lithium composite oxide sintered body plate having a thickness of 30 μm or more, a porosity of 3 to 30%, and an open pore ratio of 70% or more. Patent Document 2 (Japanese Patent No. 6374634) discloses a lithium composite oxide sintered body plate such as lithium cobalt oxide LiCoO2 (hereinafter referred to as LCO) used for the positive electrode of a lithium ion secondary battery. The lithium composite oxide sintered body plate has a structure in which multiple primary particles having a layered rock salt structure are bonded together, and is said to have a porosity of 3 to 40%, an average pore size of 15 μm or less, an open pore ratio of 70% or more, a thickness of 15 to 200 μm, and a primary particle size, which is the average particle size of the multiple primary particles, of 20 μm or less. Furthermore, this lithium composite oxide sintered plate is said to have an average angle between the (003) planes of the multiple primary particles and the plate surface of the lithium composite oxide sintered plate, i.e., an average inclination angle, which is greater than 0° and not greater than 30°.
[0004] On the other hand, it has also been proposed to use a titanium-containing sintered plate as the negative electrode. For example, Patent Document 3 (JP Patent Publication 2015-185337 A) proposes using lithium titanate (Li4Ti5O 12Patent Document 4 (Japanese Patent No. 6392493) discloses a lithium ion secondary battery using a sintered body of lithium titanate Li4Ti5O 12 The LTO sintered plate has a structure in which multiple primary particles are bonded together, and is said to have a thickness of 10 to 290 μm, a primary particle size, which is the average particle size of the multiple primary particles, of 1.2 μm or less, a porosity of 21 to 45%, and an open pore ratio of 60% or more.
[0005] Lithium ion secondary batteries have also been proposed that achieve both high discharge capacity and excellent charge / discharge cycle performance by adopting a configuration in which the positive electrode layer, separator, and negative electrode layer as a whole form a single integrated sintered plate. For example, Patent Document 5 (WO2019 / 221140A1) discloses a lithium ion secondary battery that includes a positive electrode layer made of a sintered body of a lithium composite oxide (e.g., lithium cobalt oxide), a negative electrode layer made of a titanium-containing sintered body (e.g., lithium titanate), a ceramic separator, and an electrolyte impregnated into the ceramic separator. In this battery, the positive electrode layer, the ceramic separator, and the negative electrode layer as a whole form a single integrated sintered plate, thereby bonding the positive electrode layer, the ceramic separator, and the negative electrode layer to each other. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent No. 5587052 [Patent Document 2] Patent No. 6374634 [Patent Document 3] JP 2015-185337 A [Patent Document 4] Patent No. 6392493 [Patent Document 5] WO2019 / 221140A1 Summary of the Invention
[0007] However, when attempts were made to produce an integrated sintered body type lithium ion secondary battery as disclosed in Patent Document 5 (WO2019 / 221140A1), there were problems with poor yield and long-term performance.
[0008] The present inventors have now discovered that in an integrated sintered body type lithium ion secondary battery in which a positive electrode layer, a ceramic separator, and a negative electrode layer form a single integrated sintered body as a whole, the yield and long-term performance can be improved by forming the current collecting layer into an integrated sintered body and setting the proportion of the area in which the current collecting layer and the negative electrode layer are in direct contact with each other at the bonding interface within a specified range.
[0009] Therefore, an object of the present invention is to provide an integrally sintered type lithium ion secondary battery capable of improving yield and long-term performance.
[0010] According to one aspect of the present invention, (a) a positive electrode layer composed of a sintered lithium composite oxide; a negative electrode layer composed of a titanium-containing sintered body; a ceramic separator interposed between the positive electrode layer and the negative electrode layer; an electrolyte impregnated in at least the ceramic separator; and a unit cell comprising: (b) a current collecting layer disposed on both sides of the unit cell or on the negative electrode layer side; (c) an exterior body having a sealed space and accommodating the unit cell in the sealed space; A lithium ion secondary battery comprising: the positive electrode layer, the ceramic separator, the negative electrode layer, and the current collecting layer as a whole form a single integral sintered body, whereby the positive electrode layer, the ceramic separator, the negative electrode layer, and the current collecting layer are bonded to each other; The lithium ion secondary battery is provided, in which, when a cross-section of the interface between the current collecting layer and the negative electrode layer is observed, the area where the current collecting layer and the negative electrode layer are in direct contact with each other accounts for 45 to 90% of the interface. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a schematic cross-sectional view of an example of a lithium ion secondary battery of the present invention. [Diagram 2] 1 is a SEM image showing an example of a cross section perpendicular to the layer surface of an oriented positive electrode layer. [Diagram 3] 3 is an EBSD image of a cross section of the oriented positive electrode layer shown in FIG. 2. [Figure 4] FIG. 4 is a histogram showing the distribution of orientation angles of primary particles in the EBSD image of FIG. 3 on an area basis. [Diagram 5] FIG. 2 is a schematic cross-sectional view conceptually illustrating an example of a layer structure of a laminated cell that can be used in the lithium ion secondary battery of the present invention. [Figure 6] FIG. 2 is a schematic cross-sectional view conceptually showing another example of a layer structure of a laminated cell that can be used in the lithium ion secondary battery of the present invention. [Figure 7] FIG. 2 is a schematic cross-sectional view conceptually showing another example of a layer structure of a laminated cell that can be used in the lithium ion secondary battery of the present invention. [Figure 8] FIG. 2 is a schematic cross-sectional view conceptually showing another example of a layer structure of a laminated cell that can be used in the lithium ion secondary battery of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] FIG. 1 shows a schematic diagram of an example of the lithium ion secondary battery of the present invention. The lithium ion secondary battery 10 shown in FIG. 1 is in the form of a coin-shaped battery, but the present invention is not limited thereto, and may be a battery in other forms. The lithium ion secondary battery 10 includes a unit cell 12, a current collecting layer 20 disposed on both sides of the unit cell 12 or on the surface on the negative electrode layer 18 side, and an exterior body 24. The exterior body 24 includes an enclosed space, and the unit cell 12 is housed in this enclosed space. The unit cell 12 includes a positive electrode layer 14 made of a lithium composite oxide sintered body, a ceramic separator 16, a negative electrode layer 18 made of a titanium-containing sintered body, and an electrolyte 22. The ceramic separator 16 is interposed between the positive electrode layer 14 and the negative electrode layer 18. The electrolyte 22 is impregnated into at least the ceramic separator, and typically is also impregnated into the positive electrode layer 14 and / or the negative electrode layer 18. The positive electrode layer 14, the ceramic separator 16, the negative electrode layer 18, and the current collecting layer 20 form a single integrated sintered body as a whole, which bonds the positive electrode layer 14, the ceramic separator 16, the negative electrode layer 18, and the current collecting layer 20 to each other. When the interface between the current collecting layer 20 and the negative electrode layer 18 is observed in cross section, the ratio of the area in the interface where the current collecting layer 20 and the negative electrode layer 18 are in direct contact with each other is 45 to 90%. In this way, in an integrated sintered body type lithium ion secondary battery, by forming an integrated sintered body including the current collecting layer 20 and setting the ratio of the area in the joint interface where the current collecting layer 20 and the negative electrode layer 18 are in direct contact with each other within the above range, it is possible to improve the yield and long-term performance (e.g., discharge capacity retention rate).
[0013] As mentioned above, when an attempt was made to manufacture an integrated sintered body type lithium ion secondary battery by the conventional technology, there were problems of poor yield and long-term performance. These problems are conveniently solved by the present invention. That is, one of the main causes of the decrease in yield is interfacial peeling (especially, for example, peeling at the interface between the positive electrode layer and the ceramic separator, peeling at the interface between the negative electrode layer and the ceramic separator, peeling at the interface between the positive electrode layer and the current collecting layer, and peeling at the interface between the negative electrode layer and the current collecting layer). In particular, peeling is likely to occur at the interface between the negative electrode layer and the current collecting layer. This is thought to be due to the fact that the sintered body type electrode layer necessarily has pores (due to the structure in which many primary particles are necked), and therefore there are many voids between the electrode layer (especially the negative electrode layer) and other layers. In contrast, in the lithium ion secondary battery 10 of the present invention, the positive electrode layer 14, the ceramic separator 16, the negative electrode layer 18, and the current collecting layer 20 form a single integrated sintered body as a whole, so that the positive electrode layer 14, the ceramic separator 16, the negative electrode layer 18, and the current collecting layer 20 are sufficiently bonded to each other. In addition, by setting the ratio of the area where the current collecting layer 20 and the negative electrode layer 18 directly contact each other at the bonding interface within the range of 45 to 90%, a peeling prevention effect due to sufficient contact between the negative electrode layer 18 and the current collecting layer 20 can be obtained, while adverse effects (long-term performance deterioration) caused by a direct contact area between the negative electrode layer 18 and the current collecting layer 20 being too large can be avoided. The reason why long-term performance (e.g., discharge capacity retention rate) decreases when the direct contact area between the negative electrode layer 18 and the current collecting layer 20 is too large is not clear, but it is thought that this is because stress generated during charging and discharging is likely to occur at the interface between the negative electrode layer 18 and the current collecting layer 20, making the interface peeling more likely to occur.
[0014] When the interface between the current collecting layer 20 and the negative electrode layer 18 is observed in cross section, the ratio of the area where the current collecting layer 20 and the negative electrode layer 18 are in direct contact with each other at the interface is 45 to 90%, preferably 45 to 85%, more preferably 47 to 80%, even more preferably 50 to 75%, and particularly preferably 55 to 70%. The ratio of the direct contact area can be determined by the following procedure, using a scanning electron microscope (SEM) observation and energy dispersive X-ray analysis (EDX) measurement at a 1000x field of view (125 μm×125 μm) for a cross section (cross section perpendicular to the plate surface of the electrode plate) including the current collecting layer 20 and the negative electrode layer 18 obtained by polishing with a cross-section polisher (CP). First, the current collecting layer (specified by the current collecting layer constituent elements such as Au), the negative electrode layer (specified by the negative electrode layer constituent elements such as Ti), and the voids are defined based on the obtained SEM image and EDX element mapping image. Next, determine the length L1 of the line segments of the current collecting layer that constitute the interface (hereinafter referred to as the current collecting layer interface length L1) and the total length L2 of the line segments of the interface where the current collecting layer and the negative electrode layer are in direct contact (hereinafter referred to as the direct contact length L2). The direct contact length L2 is the total length of each direct contact line segment (for example, L 21 +L 22 +…+L 2n (n is an integer) and is equal to the current collecting layer interface length L1 minus the total length L3 of the line segments of the interface where the current collecting layer and the gap come into contact. The direct contact length L2 is then divided by the current collecting layer interface length L1 and multiplied by 100 to calculate the direct contact area ratio (=100×L2 / L1). This measurement is performed at three locations on the negative electrode layer, and the average of these values is used as the direct contact area ratio of the current collecting layer / negative electrode layer interface.
[0015] The positive electrode layer 14 is made of a lithium composite oxide sintered body. The positive electrode layer 14 is made of a sintered body, which means that the positive electrode layer 14 does not contain a binder or a conductive assistant. This is because even if the green sheet contains a binder, the binder will disappear or be burned off during firing. The positive electrode layer 14 does not contain a binder, which has the advantage of being able to avoid deterioration of the positive electrode due to the electrolyte 22. The lithium composite oxide constituting the sintered body is particularly preferably lithium cobalt oxide (typically LiCoO2 (hereinafter sometimes abbreviated as LCO)). Various lithium composite oxide sintered body plates or LCO sintered body plates are known, and for example, those disclosed in Patent Document 1 (Japanese Patent No. 5587052) and Patent Document 2 (Japanese Patent No. 6374634) can be referred to.
[0016] According to a preferred embodiment of the present invention, the positive electrode layer 14, i.e., the lithium composite oxide sintered body plate, is an oriented positive electrode layer that includes a plurality of primary particles composed of a lithium composite oxide, and the plurality of primary particles are oriented with respect to the layer surface of the positive electrode layer at an average orientation angle of more than 0° and not more than 30°. FIG. 2 shows an example of a cross-sectional SEM image perpendicular to the layer surface of the oriented positive electrode layer 14, while FIG. 3 shows an electron backscatter diffraction (EBSD) image of the cross section perpendicular to the layer surface of the oriented positive electrode layer 14. FIG. 4 shows a histogram showing the distribution of the orientation angles of the primary particles 11 in the EBSD image of FIG. 3 on an area basis. In the EBSD image shown in FIG. 3, discontinuity of the crystal orientation can be observed. In FIG. 3, the orientation angle of each primary particle 11 is shown by a shade of color, and the darker the color, the smaller the orientation angle. The orientation angle is the inclination angle of the (003) plane of each primary particle 11 with respect to the layer surface direction. In addition, in FIGS. 2 and 3, the portions shown in black inside the oriented positive electrode layer 14 are pores.
[0017] The aligned positive electrode layer 14 is an aligned sintered body composed of a plurality of primary particles 11 bonded to each other. Each primary particle 11 is mainly plate-shaped, but may include those formed in a rectangular parallelepiped shape, a cubic shape, a spherical shape, etc. The cross-sectional shape of each primary particle 11 is not particularly limited, and may be rectangular, a polygon other than rectangular, circular, elliptical, or a complex shape other than these.
[0018] Each primary particle 11 is composed of a lithium composite oxide. The lithium composite oxide is an oxide represented by Li x MO2 (where 0.05 < x < 1.10, M is at least one kind of transition metal, and M typically includes one or more of Co, Ni, and Mn). The lithium composite oxide has a layered rock salt structure. The layered rock salt structure refers to a crystal structure in which lithium layers and transition metal layers other than lithium are alternately laminated with an oxygen layer in between, that is, a crystal structure in which a transition metal ion layer and a lithium single layer are alternately laminated via oxide ions (typically an α-NaFeO2 type structure, that is, a structure in which transition metals and lithium are regularly arranged in the
[0111] axis direction of the cubic rock salt type structure). Examples of the lithium composite oxide include Li x CoO2 (lithium cobaltate), Li x NiO2 (lithium nickelate), Li x MnO2 (lithium manganate), Li x NiMnO2 (lithium nickel manganate), Li x NiCoO2 (lithium nickel cobaltate), Li x CoNiMnO2 (lithium cobalt nickel manganate), Li x CoMnO2 (lithium cobalt manganate), etc. are mentioned, and particularly preferably Li x CoO2 (lithium cobaltate, typically LiCoO2). The lithium composite oxide may contain one or more elements selected from Mg, Al, Si, Ca, Ti, V, Cr, Fe, Cu, Zn, Ga, Ge, Sr, Y, Zr, Nb, Mo, Ag, Sn, Sb, Te, Ba, Bi, and W.
[0019] As shown in Figs. 3 and 4, the average value of the orientation angles of the primary particles 11, that is, the average orientation angle, is more than 0° and not more than 30°. This brings about various advantages as follows. First, since each primary particle 11 is in a state of lying inclined with respect to the thickness direction, the adhesion between each primary particle can be improved. As a result, the lithium ion conductivity between a certain primary particle 11 and other primary particles 11 adjacent to both sides of the primary particle 11 in the longitudinal direction can be improved, so that the rate characteristics can be improved. Secondly, the rate characteristics can be further improved. This is because, as described above, in the oriented positive electrode layer 14, expansion and contraction in the thickness direction is dominant over the layer surface direction when lithium ions enter and exit, so that the expansion and contraction of the oriented positive electrode layer 14 becomes smooth, and accordingly, the entry and exit of lithium ions also becomes smooth. Thirdly, the expansion and contraction of the oriented positive electrode layer 14 accompanying the entry and exit of lithium ions occurs predominantly in the direction perpendicular to the layer surface, so that stress is less likely to occur at the bonding interface between the oriented positive electrode layer 14 and the ceramic separator 16, making it easier to maintain good bonding at the interface.
[0020] The average orientation angle of the primary particles 11 is obtained by the following method. First, in an EBSD image of a rectangular region of 95 μm×125 μm observed at a magnification of 1000 times as shown in FIG. 3, three horizontal lines are drawn to divide the oriented positive electrode layer 14 into four equal parts in the thickness direction, and three vertical lines are drawn to divide the oriented positive electrode layer 14 into four equal parts in the layer surface direction. Next, the average orientation angle of the primary particles 11 is obtained by arithmetically averaging the orientation angles of all the primary particles 11 that intersect with at least one of the three horizontal lines and the three vertical lines. From the viewpoint of further improving the rate characteristics, the average orientation angle of the primary particles 11 is preferably 30° or less, more preferably 25° or less. From the viewpoint of further improving the rate characteristics, the average orientation angle of the primary particles 11 is preferably 2° or more, more preferably 5° or more.
[0021] As shown in FIG. 4, the orientation angle of each primary particle 11 may be widely distributed from 0° to 90°, but it is preferable that the majority of the orientation angles are distributed in the region of more than 0° and less than 30°. That is, when the cross section of the oriented sintered body constituting the oriented positive electrode layer 14 is analyzed by EBSD, the total area of the primary particles 11 (hereinafter referred to as low-angle primary particles) having an orientation angle of more than 0° and less than 30° with respect to the layer surface of the oriented positive electrode layer 14 among the primary particles 11 contained in the analyzed cross section is preferably 70% or more, more preferably 80% or more, relative to the total area of the primary particles 11 contained in the cross section (specifically, the 30 primary particles 11 used to calculate the average orientation angle). This makes it possible to increase the proportion of primary particles 11 with high mutual adhesion, thereby further improving the rate characteristics. In addition, it is more preferable that the total area of the low-angle primary particles having an orientation angle of 20° or less is 50% or more relative to the total area of the 30 primary particles 11 used to calculate the average orientation angle. Furthermore, the total area of the low-angle primary particles having an orientation angle of 10° or less is more preferably 15% or more of the total area of the 30 primary particles 11 used to calculate the average orientation angle.
[0022] Since each primary particle 11 is mainly plate-like, as shown in Figs. 2 and 3, the cross section of each primary particle 11 extends in a predetermined direction and is typically approximately rectangular. That is, when the cross section of the oriented sintered body is analyzed by EBSD, the total area of the primary particles 11 having an aspect ratio of 4 or more among the primary particles 11 included in the analyzed cross section is preferably 70% or more, more preferably 80% or more, of the total area of the primary particles 11 included in the cross section (specifically, the 30 primary particles 11 used to calculate the average orientation angle). Specifically, in the EBSD image shown in Fig. 3, this can further improve the mutual adhesion between the primary particles 11, and as a result, the rate characteristics can be further improved. The aspect ratio of the primary particles 11 is the value obtained by dividing the maximum Feret diameter of the primary particles 11 by the minimum Feret diameter. The maximum Feret diameter is the maximum distance between two parallel straight lines when the primary particle 11 is sandwiched between the two parallel straight lines on the EBSD image when the cross section is observed. The minimum Feret diameter is the minimum distance between two parallel lines when the primary particle 11 is sandwiched between the lines on an EBSD image.
[0023] The average particle size of the primary particles constituting the oriented sintered body is preferably 5 μm or more. Specifically, the average particle size of the 30 primary particles 11 used to calculate the average orientation angle is preferably 5 μm or more, more preferably 7 μm or more, and even more preferably 12 μm or more. This reduces the number of grain boundaries between the primary particles 11 in the direction in which lithium ions are conducted, improving the overall lithium ion conductivity, and thus improving the rate characteristics. The average particle size of the primary particles 11 is the arithmetic average of the circle-equivalent diameters of the primary particles 11. The circle-equivalent diameter is the diameter of a circle having the same area as each primary particle 11 on an EBSD image.
[0024] The positive electrode layer 14 preferably contains pores. When the sintered body contains pores, particularly open pores, the electrolyte can penetrate into the sintered body when the sintered body is incorporated into a battery as a positive electrode plate, and as a result, the lithium ion conductivity can be improved. This is because the conduction of lithium ions in the sintered body is by far faster than the conduction through the electrolyte in the pores, although there are two types of conduction: through the constituent particles of the sintered body and through the electrolyte in the pores.
[0025] The positive electrode layer 14, i.e., the lithium composite oxide sintered body, preferably has a porosity of 20 to 60%, more preferably 25 to 55%, further preferably 30 to 50%, and particularly preferably 30 to 45%. The pores are expected to provide a stress relief effect and a high capacity, and the mutual adhesion between the primary particles 11 can be further improved, thereby further improving the rate characteristics. The porosity of the sintered body is calculated by polishing the cross section of the positive electrode layer with a CP (cross section polisher) and then observing the SEM at 1000 magnifications, and binarizing the obtained SEM image. The average circle equivalent diameter of each pore formed inside the oriented sintered body is not particularly limited, but is preferably 8 μm or less. The smaller the average circle equivalent diameter of each pore, the more the mutual adhesion between the primary particles 11 can be further improved, and as a result, the rate characteristics can be further improved. The average circle equivalent diameter of the pores is the arithmetic average of the circle equivalent diameters of 10 pores on the EBSD image. The circle equivalent diameter is the diameter of a circle having the same area as each pore on the EBSD image. Each pore formed inside the oriented sintered body is preferably an open pore that communicates with the outside of the positive electrode layer 14.
[0026] The average pore size of the positive electrode layer 14, i.e., the lithium composite oxide sintered body, is preferably 0.1 to 10.0 μm, more preferably 0.2 to 5.0 μm, and further preferably 0.25 to 3.0 μm. Within the above range, local stress concentration in large pores is suppressed, and stress in the sintered body is easily released uniformly.
[0027] The thickness of the positive electrode layer 14 is preferably 20 to 1000 μm, more preferably 30 to 900 μm, and further preferably 40 to 800 μm. Within such a range, the active material capacity per unit area is increased to improve the energy density of the lithium-ion secondary battery 10, and deterioration of the battery characteristics (particularly an increase in the resistance value) due to repeated charging and discharging can be suppressed.
[0028] The negative electrode layer 18 is made of a titanium-containing sintered body. The titanium-containing sintered body is lithium titanate Li4Ti5O 12 It is preferable that the battery contains Li4Ti5O (hereinafter referred to as LTO) or niobium titanium composite oxide Nb2TiO7, and more preferably contains LTO. Although LTO is typically known to have a spinel structure, it can also adopt other structures during charging and discharging. For example, LTO is Li4Ti5O 12 (spinel structure) and Li7Ti5O 12 The reaction proceeds in the coexistence of two phases, i.e., spinel and tetrahydrofuran (rock salt structure). Therefore, LTO is not limited to a spinel structure.
[0029] The negative electrode layer 18 being made of a sintered body means that the negative electrode layer 18 does not contain a binder or a conductive additive. This is because even if the green sheet contains a binder, the binder will disappear or be burned away during firing. Since the negative electrode layer does not contain a binder, the packing density of the negative electrode active material (e.g., LTO or Nb2TiO7) becomes high, and a high capacity and good charge / discharge efficiency can be obtained. The LTO sintered body can be manufactured according to the methods described in Patent Document 3 (JP Patent Publication 2015-185337 A) and Patent Document 4 (JP Patent Publication 6392493 A).
[0030] The negative electrode layer 18, i.e., the titanium-containing sintered body, has a structure in which a plurality (i.e., a large number) of primary particles are bonded together. Therefore, it is preferable that these primary particles are composed of LTO or Nb2TiO7.
[0031] The thickness of the negative electrode layer 18 is preferably 20 to 1000 μm, more preferably 30 to 900 μm, and further preferably 40 to 800 μm. The thicker the negative electrode layer 18, the easier it is to realize a battery with a high capacity and high energy density. The thickness of the negative electrode layer 18 can be obtained, for example, by measuring the distance between layer surfaces observed to be approximately parallel when a cross section of the negative electrode layer 18 is observed by SEM (scanning electron microscope).
[0032] The primary particle size, which is the average particle size of the multiple primary particles constituting the negative electrode layer 18, is preferably 1.2 μm or less, more preferably 0.02 to 1.2 μm, and further preferably 0.05 to 0.7 μm. Within such a range, it is easy to achieve both lithium ion conductivity and electronic conductivity, which contributes to improving the rate performance.
[0033] The negative electrode layer 18 preferably contains pores. When the sintered body contains pores, particularly open pores, and is incorporated into a battery as a negative electrode layer, the electrolyte can penetrate into the sintered body, thereby improving the lithium ion conductivity. This is because the conduction of lithium ions in the sintered body is by far faster than the conduction through the electrolyte in the pores, although there are two types of conduction: through the constituent particles of the sintered body and through the electrolyte in the pores.
[0034] The porosity of the negative electrode layer 18 is preferably 20 to 60%, more preferably 30 to 55%, and further preferably 35 to 50%. Within such a range, it is easy to achieve both lithium ion conductivity and electronic conductivity, which contributes to improving the rate performance.
[0035] The average pore size of the negative electrode layer 18 is 0.08 to 5.0 μm, preferably 0.1 to 3.0 μm, and more preferably 0.12 to 1.5 μm. Within such a range, it is easy to achieve both lithium ion conductivity and electronic conductivity, which contributes to improving the rate performance.
[0036] The ceramic separator 16 is a microporous film made of ceramic. The ceramic separator 16 is advantageous in that it can be manufactured as a single integrated sintered body together with the positive electrode layer 14, the negative electrode layer 18, and the current collecting layer 20 as a whole, as well as being excellent in heat resistance. The ceramic contained in the ceramic separator 16 is preferably at least one selected from MgO, Al2O3, ZrO2, SiC, Si3N4, AlN, and cordierite, and more preferably at least one selected from MgO, Al2O3, and ZrO2. The thickness of the ceramic separator 16 is preferably 3 to 40 μm, more preferably 5 to 35 μm, and even more preferably 10 to 30 μm. The porosity of the ceramic separator 16 is preferably 30 to 85%, and more preferably 40 to 80%.
[0037] The ceramic separator 16 may contain a glass component from the viewpoint of improving the adhesion between the positive electrode layer 14 and the negative electrode layer 18. In this case, the content of the glass component in the ceramic separator 16 is preferably 0.1 to 50% by weight, more preferably 0.5 to 40% by weight, and further preferably 0.5 to 30% by weight, based on the total weight of the ceramic separator 16. The glass component is preferably added to the ceramic separator 16 by adding glass frit to the raw material powder of the ceramic separator. However, as long as the desired adhesion between the ceramic separator 16 and the positive electrode layer 14 and the negative electrode layer 18 can be ensured, it is not particularly necessary for the ceramic separator 16 to contain a glass component.
[0038] The current collecting layer 20 is disposed on both sides of the unit cell 12 or on the surface on the negative electrode layer 18 side. The current collecting layer 20 is not particularly limited as long as it is a layer containing a conductive material, but it is preferable that the current collecting layer 20 contains at least one selected from the group consisting of Au, Pt, Pd, and Cu. The thickness of the current collecting layer 20 is preferably 0.05 to 10 μm, more preferably 0.1 to 5 μm, and even more preferably 0.1 to 3 μm. The current collecting layer 20 is essential on the negative electrode layer 18 side, but the current collecting layer 20 may or may not be present on the positive electrode layer 14 side. For example, when the positive electrode layer 14 is an oriented positive electrode layer, it has excellent electronic conductivity, so that the positive electrode layer 14 itself can have a current collecting function without using the current collecting layer 20.
[0039] The electrolytic solution 22 is not particularly limited, and may be an organic solvent (for example, a mixed solvent of ethylene carbonate (EC) and methyl ethyl carbonate (MEC), a mixed solvent of ethylene carbonate (EC) and diethyl carbonate (DEC), or a mixed solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC)). medium) A lithium salt (e.g. LiPF6 )of A commercially available electrolyte for lithium batteries, such as a solution in which lithium is dissolved, may be used.
[0040] In order to obtain a lithium ion secondary battery having excellent heat resistance, the electrolyte 22 is preferably a non-aqueous solvent containing lithium borofluoride (LiBF4). In this case, the preferred non-aqueous solvent is at least one selected from the group consisting of γ-butyrolactone (GBL), ethylene carbonate (EC) and propylene carbonate (PC), more preferably a mixed solvent of EC and GBL, a single solvent of PC, a mixed solvent of PC and GBL, or a single solvent of GBL, and particularly preferably a mixed solvent of EC and GBL or a single solvent of GBL. The non-aqueous solvent contains γ-butyrolactone (GBL) to increase the boiling point and significantly improve the heat resistance. From this viewpoint, the volume ratio of EC:GBL in the non-aqueous solvent containing EC and / or GBL is preferably 0:1 to 1:1 (GBL ratio 50 to 100 volume%), more preferably 0:1 to 1:1.5 (GBL ratio 60 to 100 volume%), even more preferably 0:1 to 1:2 (GBL ratio 66.6 to 100 volume%), and particularly preferably 0:1 to 1:3 (GBL ratio 75 to 100 volume%). Lithium borofluoride (LiBF4) dissolved in the non-aqueous solvent is an electrolyte with a high decomposition temperature, which also brings about a significant improvement in heat resistance. The concentration of LiBF4 in the electrolytic solution 22 is preferably 0.5 to 2 mol / L, more preferably 0.6 to 1.9 mol / L, even more preferably 0.7 to 1.7 mol / L, and particularly preferably 0.8 to 1.5 mol / L.
[0041] The electrolyte solution 22 may further contain vinylene carbonate (VC) and / or fluoroethylene carbonate (FEC) and / or vinyl ethylene carbonate (VEC) as an additive. Both VC and FEC have excellent heat resistance. Therefore, by including such an additive in the electrolyte solution 22, an SEI film having excellent heat resistance can be formed on the surface of the negative electrode layer 18.
[0042] Also, a solid electrolyte or a polymer electrolyte may be used instead of the electrolytic solution 22 (in other words, a solid electrolyte or a polymer electrolyte may be used as the electrolyte in addition to the electrolytic solution 22). In that case, similar to the case of the electrolytic solution 22, it is preferable that the electrolyte is impregnated at least into the pores of the ceramic separator 16. The impregnation method is not particularly limited, but examples include a method of melting the electrolyte and infiltrating it into the pores of the ceramic separator 16, a method of pressing a powder compact of the electrolyte against the ceramic separator 16, and the like.
[0043] According to a preferred embodiment of the present invention, the lithium ion secondary battery 10 may have a plurality of unit cells 12 and current collecting layers 20. Such a cell stack (multilayer cell) configuration can achieve both high voltage and large current and improved rate characteristics. In this embodiment, a plurality of unit cells 12 are stacked in series or parallel via the current collecting layers 20 to form a cell stack, which is housed in an exterior body 24. In this case, it is preferable that the parts of the cell stack other than the electrolyte (i.e., the positive electrode layer 14, the ceramic separator 16, the negative electrode layer 18, and the current collecting layers 20) form a single integrated sintered body as a whole, not only from the viewpoint of improving yield and long-term performance, but also from the viewpoint of improving manufacturing efficiency (i.e., the multilayer cell can be manufactured by one firing). From the above viewpoint, the number of unit cells 12 included in the cell stack is preferably 1 to 20, more preferably 1 to 15, and even more preferably 1 to 10.
[0044] The layer structure of the cell stack is not particularly limited as long as it has a plurality of unit cells 12 (including a positive electrode layer 14, a ceramic separator 16, a negative electrode layer 18, and an electrolyte) and a current collecting layer 20. For example, as shown in FIG. 5, a plurality of unit cells 12 may be stacked in parallel with one current collecting layer 20 interposed therebetween, or as shown in FIG. 6, a plurality of unit cells 12 may be stacked in series with one current collecting layer 20 interposed therebetween. As shown in FIG. 7, a plurality of unit cells 12 each having a current collecting layer 20 formed on both sides thereof (i.e., current collecting layer 20 / unit cell 12 / current collecting layer 20) may be stacked, in which case two current collecting layers 20 are interposed between the unit cells 12. Furthermore, as shown in FIG. 8, a ceramic separator 16 may be further interposed between adjacent current collecting layers 20. In either embodiment, it is desirable to have current collecting layers 20 disposed on both sides (top and bottom) of the cell stack.
[0045] The cell stack is not limited to the flat plate stack structure in which flat plates or layers are stacked as shown in Figures 5 to 8, but may have various stack structures including the following examples. Note that in any of the configurations exemplified below, it is preferable that the entire cell stack is one integral sintered body. - Folded structure: A laminated structure in which a sheet having a layered configuration including a unit cell and a current collecting layer is folded once or multiple times to form a multilayer (large area) structure. - Wound structure: A laminated structure in which sheets having a layered configuration including a unit cell and a current collecting layer are wound and integrated to form a multi-layered (large-area) laminated structure. - Multilayer ceramic capacitor (MLCC)-like structure: A laminated structure in which a stack unit of current collecting layer / positive electrode layer / ceramic separator layer / negative electrode layer / current collecting layer is repeated in the thickness direction to form a multi-layered (large-area) structure, with multiple positive electrode layers collecting current on one side (e.g. the left side) and multiple negative electrode layers collecting current on the other side (e.g. the right side).
[0046] The exterior body 24 has a sealed space, and the positive electrode layer 14, the ceramic separator 16, the negative electrode layer 18, the current collecting layer 20, and the electrolyte 22 are accommodated in this sealed space. The exterior body 24 may be appropriately selected according to the type of the lithium ion secondary battery 10. For example, when the lithium ion secondary battery is in the form of a coin-shaped battery as shown in FIG. 1, the exterior body 24 typically has a positive electrode can 24a, a negative electrode can 24b, and a gasket 24c, and the positive electrode can 24a and the negative electrode can 24b are crimped via the gasket 24c to form a sealed space. The positive electrode can 24a and the negative electrode can 24b may be made of a metal such as stainless steel, and are not particularly limited. The gasket 24c may be a ring-shaped member made of an insulating resin such as polypropylene, polytetrafluoroethylene, or PFA resin, and are not particularly limited.
[0047] Furthermore, when the lithium ion secondary battery is in the form of a chip battery that can be built into a card, it is preferable that the exterior body is a resin substrate and the battery elements (i.e., the positive electrode layer 14, the negative electrode layer 18, the ceramic separator 16, and the electrolyte 22) are embedded in the resin substrate. For example, the battery elements may be sandwiched between a pair of resin films, and it is preferable that the resin films are bonded together with an adhesive or are heat-sealed together by a hot press.
[0048] Manufacturing method of integral sintered body The integral sintered body composed of the positive electrode layer 14, the ceramic separator 16, the negative electrode layer 18, and the current collecting layer 20 may be manufactured by any method, but is preferably manufactured by (1) preparing green sheets corresponding to the positive electrode layer 14, the ceramic separator 16, and the negative electrode layer 18, respectively, (2) forming the current collecting layer 20 on one side of the positive electrode green sheet and / or the negative electrode green sheet, (3) stacking these green sheets so that the current collecting layer 20 faces outward to form a unit laminate (corresponding to the unit cell 12), and (4) firing the obtained green sheet laminate. Alternatively, a cell laminate can be manufactured by repeating the above steps (1) to (3).
[0049] (1) Preparation of various green sheets (1a) Preparation of positive electrode green sheet The lithium composite oxide-containing green sheet as the positive electrode green sheet can be prepared as follows. First, a raw powder composed of a lithium composite oxide is prepared. This powder preferably contains pre-synthesized plate-like particles (e.g., LiCoO2 plate-like particles) having a composition LiMO2 (M is as described above). The volumetric D50 particle size of the raw powder is preferably 0.3 to 30 μm. For example, the LiCoO2 plate-like particles can be prepared as follows. First, LiCoO2 powder is synthesized by mixing Co3O4 raw powder and Li2CO3 raw powder and sintering (500 to 900°C, 1 to 20 hours). The obtained LiCoO2 powder is pulverized in a pot mill to a volumetric D50 particle size of 0.2 μm to 10 μm, thereby obtaining plate-like LiCoO2 particles capable of conducting lithium ions parallel to the plate surface. Such LiCoO2 particles can be obtained by a method of growing a green sheet using LiCoO2 powder slurry and then crushing it, or by a method of synthesizing plate-like crystals such as the flux method, hydrothermal synthesis, single crystal growth using a melt, and the sol-gel method. The obtained LiCoO2 particles are in a state that is easy to cleave along the cleavage plane. LiCoO2 plate-like particles can be produced by cleaving the LiCoO2 particles by crushing.
[0050] The plate-like particles may be used alone as the raw material powder, or a mixture of the plate-like powder and other raw material powders (e.g., Co3O4 particles) may be used as the raw material powder. In the latter case, it is preferable to make the plate-like powder function as a template particle for providing orientation, and make the other raw material powders (e.g., Co3O4 particles) function as matrix particles that can grow along the template particle. In this case, it is preferable to use a powder in which the template particle and the matrix particle are mixed at 100:0 to 3:97 as the raw material powder. When the Co3O4 raw material powder is used as the matrix particle, the volume-based D50 particle size of the Co3O4 raw material powder is not particularly limited, and can be, for example, 0.1 to 1.0 μm, but is preferably smaller than the volume-based D50 particle size of the LiCoO2 template particle. The matrix particle can also be obtained by subjecting the Co(OH)2 raw material to heat treatment at 500°C to 800°C for 1 to 10 hours. In addition to Co3O4, Co(OH)2 particles or LiCoO2 particles may be used as the matrix particle.
[0051] When the raw powder is composed of 100% LiCoO2 template particles, or when LiCoO2 particles are used as matrix particles, a large (e.g., 90 mm x 90 mm square) and flat LiCoO2 sintered body layer can be obtained by sintering. Although the mechanism is unclear, it is expected that volume change or local unevenness during sintering is unlikely to occur because LiCoO2 is not synthesized during the sintering process.
[0052] The raw powder is mixed with a dispersion medium and various additives (binder, plasticizer, dispersant, etc.) to form a slurry. A lithium compound other than LiMO2 (e.g., lithium carbonate) may be added to the slurry in an excess amount of about 0.5 to 30 mol % for the purpose of promoting grain growth or compensating for volatile matter during the firing process described later. It is preferable not to add a pore former to the slurry. The slurry is preferably stirred under reduced pressure to defoam it and adjusted to a viscosity of 4000 to 10000 cP. The obtained slurry is molded into a sheet to obtain a lithium composite oxide-containing green sheet. The sheet molding is preferably performed using a molding method capable of applying a shear force to plate-like particles (e.g., template particles) in the raw powder. By doing so, the average inclination angle of the primary particles can be made to be more than 0° and 30° or less with respect to the sheet surface. The doctor blade method is suitable as a molding method capable of applying a shear force to the plate-like particles. The thickness of the lithium composite oxide-containing green sheet may be appropriately set so as to have the desired thickness as described above after firing.
[0053] (1b) Preparation of negative electrode green sheet The titanium-containing green sheet as the negative electrode green sheet may be produced by any method. For example, the LTO-containing green sheet can be produced as follows. First, lithium titanate Li4Ti5O 12A raw powder (LTO powder) consisting of the above is prepared. The raw powder may be a commercially available LTO powder or may be newly synthesized. For example, a powder obtained by hydrolyzing a mixture of titanium tetraisopropoxy alcohol and isopropoxy lithium may be used, or a mixture containing lithium carbonate, titania, etc. may be fired. The volumetric D50 particle size of the raw powder is preferably 0.05 to 5.0 μm, more preferably 0.1 to 2.0 μm. If the particle size of the raw powder is large, the pores tend to become large. In addition, if the raw particle size is large, a pulverization process (for example, pot mill pulverization, bead mill pulverization, jet mill pulverization, etc.) may be performed to obtain a desired particle size. Then, the raw powder is mixed with a dispersion medium and various additives (binder, plasticizer, dispersant, etc.) to form a slurry. A lithium compound other than LiMO2 (for example, lithium carbonate) may be added to the slurry in an excess of about 0.5 to 30 mol% for the purpose of promoting particle growth or compensating for volatiles during the firing process described later. It is preferable not to add a pore former to the slurry. The slurry is preferably stirred under reduced pressure to degas and adjusted to a viscosity of 4000 to 10000 cP. The obtained slurry is formed into a sheet to obtain an LTO-containing green sheet. The sheet can be formed by various known methods, but is preferably formed by a doctor blade method. The thickness of the LTO-containing green sheet may be appropriately set so that it has the desired thickness as described above after firing.
[0054] (1c) Preparation of separator green sheets The separator green sheet can be prepared as follows. First, at least one ceramic powder selected from MgO, Al2O3, ZrO2, SiC, Si3N4, AlN, and cordierite is prepared. Glass frit may be added to this ceramic powder. The volume-based D50 particle size of the raw material powder is preferably 0.05 to 20 μm, more preferably 0.1 to 10 μm. If the particle size of the raw material powder is large, the pores tend to become large. If the raw material particle size is large, a pulverization process (for example, pot mill pulverization, bead mill pulverization, jet mill pulverization, etc.) may be performed to obtain a desired particle size. Then, the raw material powder is mixed with a dispersion medium and various additives (binder, plasticizer, dispersant, etc.) to form a slurry. It is preferable that no pore former is added to the slurry. The slurry is stirred under reduced pressure to defoam it, and the viscosity is preferably adjusted to 4000 to 10000 cP. The obtained slurry is formed into a sheet to obtain a separator green sheet. The sheet forming can be performed by various well-known methods, but is preferably performed by a doctor blade method. The thickness of the separator green sheet may be appropriately set so that it has a desired thickness as described above after firing.
[0055] (2) Formation of the current collecting layer The current collecting layer is not particularly limited as long as it is a layer containing a conductive material, but is preferably one that forms a metal layer by firing. The current collecting layer may be formed by applying a metal paste (e.g., Au paste, Pt paste, Pd paste, or Cu paste) to one side of the positive electrode green sheet and / or the negative electrode green sheet. The metal paste may be applied by any method, but it is preferable to apply it by printing, since it is possible to form a current collecting layer with a highly precisely controlled thickness with high productivity. The current collecting layer may be formed on one or both sides of the green sheet laminate after the green sheet laminate is formed.
[0056] (3) Stacking and compression of green sheets Next, the positive electrode green sheet, the separator green sheet, and the negative electrode green sheet ToThe green sheets are stacked in order, and the resulting laminate is pressed to bond the green sheets together. The pressing may be performed by any known method, and is not particularly limited, but is preferably performed by CIP (cold isostatic pressing). The preferred pressing pressure is 10 to 5000 kgf / cm. 2 and more preferably 50 to 3000 kgf / cm 2 It is preferable to punch out the green sheet laminate thus compressed into a desired shape (for example, a coin shape or a chip shape) or size using a punching die. By doing so, it is possible to eliminate the misalignment between the positive electrode layer 14 and the negative electrode layer 18 in the final integrated sintered body. As a result, the end faces of the positive electrode layer 14 and the negative electrode layer 18 are aligned, maximizing the capacity of the battery.
[0057] (4) Firing of the green sheet laminate The obtained green sheet laminate (including the current collecting layer) is placed on a setter. The setter is made of ceramics, preferably zirconia or magnesia. The setter is preferably embossed. The green sheet thus placed on the setter is placed in a sheath. The sheath is also made of ceramics, preferably alumina. In this state, the green sheet is degreased as desired and then fired to obtain an integrated sintered body. The degreasing is preferably carried out by holding at 300 to 600°C for 0.5 to 20 hours. The firing is preferably carried out at 650 to 900°C for 0.01 to 20 hours, more preferably at 700 to 850°C for 0.5 to 10 hours. The temperature rise rate during firing is preferably 50 to 1500°C / h, more preferably 200 to 1300°C / h. In particular, this temperature rise rate is preferably adopted in the temperature rise process of 600 to 900°C, more preferably in the temperature rise process of 600 to 800°C. In this way, an integrated sintered body consisting of the positive electrode layer 14, the ceramic separator 16, the negative electrode layer 18, and the current collecting layer 20 is obtained. If the punching process is not performed at the stage of the green sheet laminate described above, a misalignment may occur between the positive electrode layer 14 and the negative electrode layer 18 in the final integrated sintered body. In this case, it is preferable to finish the end faces of the integrated sintered body by a method such as laser processing, cutting, or polishing to minimize or eliminate the misalignment. As a result, the end faces of the positive electrode layer 14 and the end faces of the negative electrode layer 18 are aligned, thereby maximizing the capacity of the battery. EXAMPLES
[0058] The present invention will be described more specifically with reference to the following examples. In the following examples, LiCoO2 is abbreviated as "LCO" and Li4Ti5O 12 shall be abbreviated as "LTO."
[0059] Example 1 (1) Preparation of LCO green sheet (positive electrode green sheet) First, Co3O4 powder (manufactured by Seido Chemical Industry Co., Ltd.) and Li2CO3 powder (manufactured by Honjo Chemical Co., Ltd.) were mixed so that the molar ratio of Li / Co was 1.01, and then the mixture was kept at 780°C for 5 hours. The obtained powder was pulverized in a pot mill so that the volumetric D50 was 0.4 μm to obtain a powder consisting of LCO plate-like particles. 100 parts by weight of the obtained LCO powder, 100 parts by weight of a dispersion medium (toluene: isopropanol = 1:1), 12 parts by weight of a binder (polyvinyl butyral: product number BM-2, manufactured by Sekisui Chemical Co., Ltd.), 4 parts by weight of a plasticizer (DOP: Di (2-ethylhexyl) phthalate, manufactured by Kurogane Kasei Co., Ltd.), and 2 parts by weight of a dispersant (product name Rheodol SP-O30, manufactured by Kao Corporation) were mixed. The obtained mixture was stirred under reduced pressure to defoam it, and the viscosity was adjusted to 4000 cP to prepare an LCO slurry. The viscosity was measured using a Brookfield LVT viscometer. The slurry thus prepared was formed into a sheet on a PET film by a doctor blade method to form an LCO green sheet. The thickness of the LCO green sheet was adjusted to 120 μm after firing.
[0060] (2) Preparation of LTO green sheet (negative electrode green sheet) First, 100 parts by weight of LTO powder (volume standard D50 particle size 0.06 μm, manufactured by Sigma-Aldrich Japan LLC), 100 parts by weight of dispersion medium (toluene: isopropanol = 1:1), 20 parts by weight of binder (polyvinyl butyral: product number BM-2, manufactured by Sekisui Chemical Co., Ltd.), 4 parts by weight of plasticizer (DOP: Di (2-ethylhexyl) phthalate, manufactured by Kurogane Kasei Co., Ltd.), and 2 parts by weight of dispersant (product name Rheodol SP-O30, manufactured by Kao Corporation) were mixed. The obtained negative electrode raw material mixture was stirred and degassed under reduced pressure, and the viscosity was adjusted to 4000 cP to prepare an LTO slurry. The viscosity was measured with an LVT type viscometer manufactured by Brookfield. The slurry thus prepared was formed into a sheet shape on a PET film by the doctor blade method to form an LTO green sheet. The thickness of the LTO green sheet was set so that the thickness after firing was 140 μm.
[0061] (3) Preparation of MgO green sheet (separator green sheet) Magnesium carbonate powder (manufactured by Konoshima Chemical Co., Ltd.) was heat-treated at 900°C for 5 hours to obtain MgO powder. The obtained MgO powder and glass frit (manufactured by Nippon Frit Co., Ltd., CK0199) were mixed at a weight ratio of 4:1. 100 parts by weight of the obtained mixed powder (volume-based D50 particle size 0.4 μm), 100 parts by weight of a dispersion medium (toluene: isopropanol = 1:1), 20 parts by weight of a binder (polyvinyl butyral: product number BM-2, manufactured by Sekisui Chemical Co., Ltd.), 4 parts by weight of a plasticizer (DOP: Di (2-ethylhexyl) phthalate, manufactured by Kurogane Kasei Co., Ltd.), and 2 parts by weight of a dispersant (product name Rheodol SP-O30, manufactured by Kao Corporation) were mixed. The obtained raw material mixture was stirred under reduced pressure to defoam it, and the viscosity was adjusted to 4000 cP to prepare a slurry. The viscosity was measured with a Brookfield LVT type viscometer. The slurry thus prepared was formed into a sheet on a PET film by a doctor blade method to form a separator green sheet, the thickness of which was adjusted to 15 μm after firing.
[0062] (4) Formation of the current collecting layer Au paste (manufactured by Tanaka Kikinzoku Co., Ltd., product name: GB-2706) was printed on one side of the LCO green sheet (positive electrode green sheet) and the LTO green sheet (negative electrode green sheet) using a printer. The thickness of the printed layer was set to 0.5 μm after firing.
[0063] (5) Lamination, compression and firing The LCO green sheet (positive electrode green sheet), MgO green sheet (separator green sheet) and LTO green sheet (negative electrode green sheet) were stacked in this order with the current collecting layer facing outward, and the resulting laminate was subjected to CIP (cold isostatic pressing) at 200 kgf / cm 2The green sheets were pressed together with a press. The laminate thus pressed was punched out into a disk shape with a diameter of 10 mm using a punching die. The obtained disk-shaped laminate was degreased at 600°C for 5 hours, and then heated to 800°C at 1000°C / h and held there for 10 minutes, after which it was cooled. In this way, an integrated sintered body was obtained, consisting of a positive electrode layer (LCO sintered body layer), a ceramic separator (MgO separator), a negative electrode layer (LTO sintered body layer), and a current collecting layer (Au layer).
[0064] (6) Fabrication of lithium-ion secondary batteries A coin-type lithium-ion secondary battery 10 as shown in FIG. 1 was fabricated as follows. A positive electrode current collector layer, an integrated sintered plate (LCO positive electrode layer, MgO separator, and LTO negative electrode layer), and a negative electrode current collector layer were stacked in this order between the positive electrode can and the negative electrode can that constitute the battery case, and after filling with an electrolyte, the positive electrode can and the negative electrode can were crimped via a gasket to seal. In this way, a coin cell-type lithium-ion secondary battery 10 with a diameter of 20 mm and a thickness of 3.2 mm was fabricated. At this time, the electrolyte used was a solution obtained by dissolving LiBF4 to a concentration of 1.5 mol / L in an organic solvent in which ethylene carbonate (EC) and γ-butyrolactone (GBL) were mixed in a volume ratio of 1:3.
[0065] (6) Evaluation The LCO sintered compact layer (positive electrode layer), the LTO sintered compact layer (negative electrode layer), and the MgO separator (ceramic separator) synthesized in the above (5), and the coin-type lithium-ion secondary battery fabricated in the above (6) were evaluated in various ways as shown below.
[0066] <Average orientation angle of primary particles> The LCO sintered body layer was polished with a cross-section polisher (CP) (IB-15000CP, manufactured by JEOL Ltd.), and the cross section of the obtained positive electrode layer (cross section perpendicular to the layer surface of the positive electrode layer) was measured by EBSD at a magnification of 1000 times (125 μm × 125 μm) to obtain an EBSD image. This EBSD measurement was performed using a Schottky field emission scanning electron microscope (JSM-7800F, manufactured by JEOL Ltd.). For all particles identified in the obtained EBSD image, the angle between the (003) plane of the primary particle and the layer surface of the positive electrode layer (i.e., the inclination of the crystal orientation from (003)) was calculated as the inclination angle, and the average value of these angles was taken as the average orientation angle of the primary particles. As a result, the average orientation angle of the primary particles in the positive electrode layer was 16°.
[0067] <Layer thickness> The LCO and LTO sintered body layers and the MgO separator were polished with a cross-section polisher (CP) (JEOL Ltd., IB-15000CP), and the cross sections were observed with an SEM (JEOL Ltd., JSM6390LA) to measure the thicknesses of the positive electrode layer, the negative electrode layer, and the separator. As a result, the thickness of the positive electrode layer was 60 μm, the thickness of the negative electrode layer was 70 μm, and the thickness of the ceramic separator was 15 μm.
[0068] <Porosity> The LCO or LTO sintered body layer and the MgO separator were polished with a cross-section polisher (CP) (JEOL Ltd., IB-15000CP), and the cross section of the obtained positive electrode layer or negative electrode layer was observed with a SEM (JEOL Ltd., JSM6390LA) at a magnification of 1000 times (125 μm × 125 μm). The obtained SEM image was analyzed, and the area of all pores was divided by the area of the positive electrode or negative electrode, and the porosity (%) was calculated by multiplying the obtained value by 100. As a result, the porosity of the positive electrode layer was 45%, the porosity of the negative electrode layer was 45%, and the porosity of the ceramic separator was 50%.
[0069] <Average pore diameter> The average pore diameter of the LCO or LTO sintered body layer was measured by mercury intrusion method using a mercury porosimeter (Shimadzu Corporation, Autopore IV9510). As a result, the average pore diameter of the positive electrode layer was 0.8 μm, the average pore diameter of the negative electrode layer was 0.5 μm, and the average pore diameter of the ceramic separator was 0.2 μm.
[0070] <Proportion of direct contact area at the interface between current collecting layer and negative electrode layer> The integral sintered body was polished with a cross-section polisher (CP) (IB-15000CP, manufactured by JEOL Ltd.) to form a polished cross section (cross section perpendicular to the plate surface of the electrode plate) including the current collecting layer and the negative electrode layer. This polished cross section was observed with a SEM (JSM-IT500LA, manufactured by JEOL Ltd.) at a magnification of 1000 times (125 μm × 125 μm) and measured with EDX. Based on the obtained SEM image and EDX element mapping image, the current collecting layer (Au), electrode layer (Ti), and void regions were defined, and the length L1 of the line segment of the current collecting layer (Au) constituting the interface (hereinafter referred to as current collecting layer interface length L1) and the total length L2 of the line segments of the interface where the current collecting layer (Au) and the negative electrode layer (Ti) are in direct contact with each other (hereinafter referred to as direct contact length L2) were determined. The direct contact length L2 is the total length of each direct contact line segment (for example, L 21 +L 22 +…+L 2n (n is an integer) and is equal to the current collecting layer interface length L1 minus the total length L3 of the line segments of the interface where the current collecting layer and the gap come into contact. The direct contact length L2 was divided by the current collecting layer interface length L1 and multiplied by 100 to calculate the direct contact area ratio (=100×L2 / L1). This measurement was performed at three locations on the negative electrode layer, and the average value was used as the direct contact area ratio of the current collecting layer / negative electrode layer interface.
[0071] <Yield evaluation> The fabricated batteries were subjected to visual inspection and battery inspection to evaluate the yield. 20 battery samples were evaluated for each inspection, and a battery was judged to have passed if 80% or more of the samples passed both inspections. The results are shown in Table 1.
[0072] (1) Visual inspection For each electrode structure, the interface between the positive electrode layer and the ceramic separator, the interface between the negative electrode layer and the ceramic separator, the interface between the positive electrode layer and the current collector layer, and the interface between the negative electrode layer and the current collector layer were observed to determine whether the electrode structure was integrated without peeling. Electrode structures that were integrated without interfacial peeling were determined to be good products.
[0073] (2) Battery inspection The resistance value R30 at 1 Hz when the SOC (state of charge) was 30% was measured by AC impedance measurement. The resistance value (Ω cm 2 ) was calculated. Batteries whose resistance value was within 20% increase from the resistance value of the reference battery were judged to be good products. Note that the reference battery used was a battery with the same current collection structure as that disclosed in the examples of Patent Document 5 (WO2019 / 221140A1) (a battery in which the current collection layer does not constitute an integral sintered body, and aluminum foil as the current collection layer is bonded to the positive electrode layer and negative electrode layer of the integral sintered body (unit cell) using conductive carbon paste).
[0074] <Long-term performance evaluation> The prepared battery was charged at a constant voltage of 2.7 V, and then discharged at a discharge rate of 0.2 C to measure the initial discharge capacity. After that, the battery was charged at a constant voltage of 2.7 V, and then cycled 500 times at a discharge rate of 1 C. The battery was then charged at a constant voltage of 2.7 V, and then discharged at a discharge rate of 0.2 C to measure the post-cycle discharge capacity. The post-cycle discharge capacity was divided by the initial discharge capacity, and the value multiplied by 100 was determined to be more than 70% to be a good product. This evaluation was performed on 20 batteries, and batteries that were 80% or more good were determined to be pass. The results are shown in Table 1.
[0075] Example 2 A battery was produced and evaluated in the same manner as in Example 1, except that the stacking, compression bonding, and firing steps in (5) above were carried out as follows to form a cell stack (stacked cell) including three unit cells. The results are shown in Table 1.
[0076] (5') Lamination, compression and firing An LCO green sheet (positive electrode green sheet), an MgO green sheet (separator green sheet), and an LTO green sheet (negative electrode green sheet) were stacked in this order with the current collecting layer facing outward to obtain a unit laminate. Three such unit laminates were produced. These laminates were stacked and subjected to CIP (cold isostatic pressing) at 200 kgf / cm 2 The green sheets were pressed together with a press. The laminate thus pressed was punched out into a disk shape with a diameter of 10 mm using a punching die. The obtained disk-shaped laminate was degreased at 600°C for 5 hours, and then heated to 800°C at 1000°C / h and held there for 10 minutes, after which it was cooled. In this way, an integrated sintered body was obtained, consisting of a positive electrode layer (LCO sintered body layer), a ceramic separator (MgO separator), a negative electrode layer (LTO sintered body layer), and a current collecting layer (Au layer).
[0077] Example 3 A battery was produced and evaluated in the same manner as in Example 1, except that the lamination, compression bonding, and firing steps in (5) above were carried out as follows to form a wound cell. The results are shown in Table 1.
[0078] (5'') Lamination, compression and firing An LCO green sheet (positive electrode green sheet), an MgO green sheet (separator green sheet), and an LTO green sheet (negative electrode green sheet) were stacked in this order with the current collecting layer facing outward to obtain a unit laminate. Three such unit laminates were produced. These laminates were stacked and subjected to CIP (cold isostatic pressing) at 200 kgf / cm 2The green sheets were pressed together with a press. The laminate thus pressed was heated on a hot plate at 90°C, and then wound in a winding machine to obtain a laminate with dimensions of 10 mm outer diameter and 2.0 mm thickness. This wound laminate was degreased at 600°C for 5 hours, then heated to 800°C at 1000°C / h and held for 10 minutes for firing, and then cooled. Thus, one integral sintered body consisting of a positive electrode layer (LCO sintered body layer), a ceramic separator (MgO separator), a negative electrode layer (LTO sintered body layer), and a current collecting layer (Au layer) was obtained.
[0079] Example 4 A battery was produced and evaluated in the same manner as in Example 1, except that the LTO green sheet (negative electrode green sheet) in (2) above was produced as follows, and the maximum temperature in the firing in (5) above was set to 900° C. The results are shown in Table 1.
[0080] (2') Preparation of LTO green sheet (negative electrode green sheet) First, LTO powder (volume-based D50 particle size 0.06 μm, manufactured by Sigma-Aldrich Japan LLC) (hereinafter referred to as "raw powder") was prepared. A part of this raw powder was heat-treated at 900°C for 5 hours, and then crushed in a pot mill to D50: 2.0 μm to prepare powder A. Powder A and the raw powder were weighed and mixed in a weight ratio of 50:50 to obtain an LTO mixed powder. 100 parts by weight of the LTO mixed powder, 100 parts by weight of a dispersion medium (toluene: isopropanol = 1:1), 20 parts by weight of a binder (polyvinyl butyral: product number BM-2, manufactured by Sekisui Chemical Co., Ltd.), 4 parts by weight of a plasticizer (DOP: Di (2-ethylhexyl) phthalate, manufactured by Kurogane Kasei Co., Ltd.), and 2 parts by weight of a dispersant (product name Rheodol SP-O30, manufactured by Kao Corporation) were mixed. The obtained negative electrode raw material mixture was stirred under reduced pressure to degas it and adjust the viscosity to 4000 cP to prepare an LTO slurry. The viscosity was measured using a Brookfield LVT viscometer. The thus prepared slurry was formed into a sheet on a PET film by a doctor blade method to form an LTO green sheet. The thickness of the LTO green sheet was adjusted to 140 μm after firing.
[0081] Example 5 A battery was produced and evaluated in the same manner as in Example 4, except that in the preparation of the LTO green sheet (negative electrode green sheet) in (2') above, the mixing ratio (weight ratio) of Powder A to the raw material powder was 80:20, and the maximum temperature in the firing in (5) above was 800° C. The results are shown in Table 1.
[0082] Example 6 (comparison) In the preparation of the LTO green sheet (negative electrode green sheet) in the above (2'), the mixing ratio (weight ratio) of the powder A to the raw material powder was set to 90:10, and the amount of the binder (polyvinyl butyral) added was set to 16 parts by weight. In the firing step in the above (5), high temperature A battery was produced and evaluated in the same manner as in Example 4, except that the heating temperature was 750° C. The results are shown in Table 1.
[0083] Example 7 (comparison) A battery was produced and evaluated in the same manner as in Example 4, except that in the preparation of the LTO green sheet (negative electrode green sheet) in (2') above, the mixing ratio (weight ratio) of Powder A to the raw material powder was 25:75, the amount of binder (polyvinyl butyral) added was 16 parts by weight, and the maximum temperature in the firing in (5) above was 1000° C. The results are shown in Table 1.
[0084] [Table 1]
Claims
1. (a) a positive electrode layer composed of a sintered lithium composite oxide; a negative electrode layer having a porosity of 20 to 60% and composed of a titanium-containing sintered body; a ceramic separator interposed between the positive electrode layer and the negative electrode layer, the ceramic separator including at least one selected from the group consisting of MgO, Al 2 O 3 , ZrO 2 , SiC, Si 3 N 4 , AlN, and cordierite; an electrolyte impregnated in at least the ceramic separator; A unit cell comprising: (b) a current collecting layer disposed on both sides of the unit cell or on the negative electrode layer side of the unit cell; (c) an exterior body having a sealed space and accommodating the unit cell in the sealed space; A lithium ion secondary battery comprising: the positive electrode layer, the ceramic separator, the negative electrode layer, and the current collecting layer as a whole form a single integral sintered body, whereby the positive electrode layer, the ceramic separator, the negative electrode layer, and the current collecting layer are bonded to each other; a ratio of an area where the current collecting layer and the negative electrode layer are in direct contact with each other to 45 to 90% in a cross-section of the interface between the current collecting layer and the negative electrode layer.
2. 2. The lithium ion secondary battery according to claim 1, wherein the lithium composite oxide is lithium cobalt oxide.
3. The lithium ion secondary battery according to claim 1 or 2, wherein the positive electrode layer has a thickness of 20 to 1000 μm.
4. The lithium ion secondary battery according to any one of claims 1 to 3, wherein the negative electrode layer has a thickness of 20 to 1000 µm.
5. The lithium ion secondary battery according to any one of claims 1 to 4, wherein the titanium-containing sintered body contains lithium titanate or niobium titanium composite oxide.
6. The lithium ion secondary battery according to any one of claims 1 to 5, wherein the ceramic separator has a thickness of 3 to 40 µm.
7. The lithium ion secondary battery according to any one of claims 1 to 6, comprising a plurality of the unit cells and the current collecting layers, the plurality of unit cells being stacked in series or parallel via the current collecting layers to form a cell stack which is housed in the exterior body, and a portion of the cell stack other than the electrolyte solution forms a single integral sintered body as a whole.
8. The lithium ion secondary battery according to claim 7, wherein the number of unit cells included in the cell stack is 1 to 10.
Citation Information
Patent Citations
Measuring circuit for instantaneous power
JP1980087052A
Spot weldable composite type vibration-damping material
JP1988074634A
Thermal transfer recording medium
JP1988092493A
All-solid battery
JP2015185337A
Slurry, laminate green sheet, all-solid type secondary battery and manufacturing methods thereof
JP2018073512A